ETIKA PERGAULAN LAKI-LAKI DAN PEREMPUAN DALAM AL-QUR'AN (Analisis QS. An-Nûr ayat 31-32 Perspektif Penafsiran Hasbi Ash-Shiddiqie Dalam KitabTafsîr An-Nûr) - Eka Sulistiyawati (Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
The relationship men and women has recently been widely discussed. Interaction between humans is very necessary because humans are essentially social creatures. However, there are ethics and rules when interacting with other people. In fact, there are many interactions between members of the opposite sex who forget the rules of the shariâ and even go beyond the boundaries of correct social interaction according to the teachings of the Koran. So there are many cases of free sex and womengetting pregnant out of wedlock due to illegal socializing and this a form of lack of ethics in socializing. This research aims to understand more deeply the ethics of male and female relationships by referring to one of the tafsir books, namely Tafsir al- Majid al-Qurân An-Nûr. The method used is a qualitative method white the type of library research. The result of this research are in accordance whit the interpretation of Ash-Shiddiqie QS. An-Nûr verses 30-31 explain the ethics for a woman to always maintain her views and honor when interacting with the opposite sex. What is meant by maintaining one's gaze is not diverting one's gaze to something that can arouse lust and not giving honor to men who are not one's mahram.